Systematic review: a review of adolescent behavior change interventions [BCI] and their effectiveness in HIV and AIDS prevention in sub-Saharan Africa - M. Mwale; A. S. Muula (BMC, 2017)
Abstract Background Despite sub-Saharan Africa [SSA] constituting just 12% of the world's population, the region has the highest burden of HIV with 70% of HIV infection in general and 80% of new infections among young people occuring in the region. Diverse intervention programmes have been implemented among young people but with minimal translation to behavior change. A systematic review of Behavior Change Interventions [BCI] targeting adolescents in SSA was therefore conducted with the objective of delineating this intervention vis-a-vis efficacy gap. Methods From April to July 2015 searches were made from different journals online. Databases searched included MEDLINE, EBSCOhost, PsychINFO, Cochrane, and Google Scholar; Cambridge and Oxford journal websites, UNAIDS and WHO for studies published between 2000 and 2015. After excluding other studies by review of titles and then abstracts, the studies were reduced to 17. Three of these were randomized trials and five quasi-experimental. Overall interventions included those prescribing life skills, peer education [n = 6] and community collaborative programmes. The main study protocol was approved by the University of Malawi College of Medicine Ethics Committee on 30th June 2016 [ref #: P.01/16/1847. The review was registered with PROSPERO [NIH] in 2015. Results The review yielded some 200 titles and abstracts, 20 full text articles were critically analysed and 17 articles reviewed reflecting a dearth in published studies in the area of psychosocial BCI interventions targeting adolescents in SSA. Results show that a number of reviewed interventions [n = 8] registered positive outcomes in both knowledge and sexual practices. Conclusions The review demonstrates a paucity of psychosocial BCI studies targeting adolescents in SSA. There are however mixed findings about the effectiveness of psychosocial BCI targeting adolescents in SSA. Other studies portray intervention effectiveness and others limited efficacy. Peer education as an intervention stands out as being more effective than other psychosocial regimens, like life skills, in facilitating HIV risk reduction. There is therefore need for further research on interventions employing peer education to substantiate their potential efficacy in HIV risk reduction among adolescents. PROSPERO registration number CRD42015019244, available from http://www.crd.york.ac.uk/PROSPERO/display_record.asp?ID=CRD42015019244 .